Agency and creativity: An eye on gender identity in four Egyptian novels - Mosalem, Maha (AUC Knowledge Fountain, 2019)
For most scholars, agency is a term that has most traditionally been coined with free will, resistance, and intentionality (Giddens, 1979; Ahearn, 2001). In this study, however, the construct is examined from a linguistic perspective aiming at exploring its creative dimensions in relation to gender identity in four Egyptian novels; Bayna ʔal-qaṣrayn (Palace Walk), ʔal-Bāb ʔal-maftūḥ (The Open Door), ʔu:ri:du rajulan (I Need a Man), and ʃaġaf (Passion). By adopting a mediated discourse analysis approach (MDA) (Scollon, 2002), this study examined the connections between discourse and action in social interactions. Using the grammatical, semantic, and discursive analysis, the examination focused on representations of agency emerging in contexts and dialogic interactions. For the grammatical investigation, the study followed Dixon’s (1994) classification of the subject as well as the category of voice while the semantic strategies included the semantic roles of the subject, verb types, and sentence moods for an interpretation of further character dimension. In addition, three discourse strategies were utilized, i.e. dialogicality, parallelism, foregrounding and backgrounding, the aim of which was to understand the macro-context of subjects’ actions. Based on this examination, the study identified five creative forms of agency characteristic of gender identity. For Amina in Bayna ʔal-qaṣrayn (Palace Walk), agency is associated with her maternal powers, whereas agency is relevant to self-actualization for Layla in ʔal-Bāb ʔal-maftūḥ (The Open Door). For Amina’s ʔu:ri:du rajulan (I Need a Man), the construct is associated with revenge. Finally, love and ambition are two terms through which the protagonist in ʃaġaf (Passion), Zaynab, exercised her power.